Transmisi Budaya dan Kearifan Lokal pada Pendidikan Islam Anak Usia Dini - Sriyati Dwi Astuti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
This study aims to find out awareness of teacher of Early Childhood Education in transmitting culture and local wisdom. Through field studies approach on al-Hidayah Early Childhood Education Institute which is located in the village of Kauman, Argomulyo, Cangkringan, Sleman, it was concluded that teachers in general do not understand its importance as a transmitter of culture.